Pengaruh Pemodelan Soil-Structure Interaction pada Kinerja Struktur: Studi Kasus Tipologi Bangunan Sekolah Indonesia - Ulza, Adrian; Yunita, Halida; Idris, Yunita; Faradiba, Ratu Shara (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2025)
This study evaluates the impact of Soil-Structure Interaction (SSI) on the dynamic response of low-rise school buildings in Indonesia. Three SSI models were developed: spring supports (SSI I), distributed springs on a plate (SSI II), and soil modeled as solid elements (SSI III), compared to a benchmark model. The analysis revealed that SSI III produced the highest displacement, shear force, and overturning moment responses but required significantly longer computation time. In contrast, SSI II demonstrated more efficient results by reducing internal forces and structural displacement. This study provides insights into the implementation and contribution of SSI modeling in structural analysis.